Healthcare Professionals and Mobbing - Fedayi Yağar; Sema Dökme (Association of Nurse Managers, 2019)
INTRODUCTION: This study was conducted to evaluate research articles related to mobbing on healthcare professionals in Turkey using the content analysis method. METHODS: National and international scientific articles published between 2009-2018 were searched using PubMed, Science Direct and Google Academic databases between 01.02.2018 - 01.04.2018. When searching, the keywords "mobbing in hospitals, mobbing in health institutions, health professionals and mobbing, physicians and mobbing, nurses and mobbing" were used. In this context, it was decided that 56 research articles could be used in the study by taking into consideration the various restrictions. RESULTS: In the study, the majority of studies was observed to be conducted in public institutions. In terms of the research design, almost all were found to be carried out with quantitative research methodology. It was observed that nurses constitute the most studied occupational group in these studies. It was determined that there were very few studies conducted especially with physicians and administrative staff. DISCUSSION AND CONCLUSION: It was observed in the studies that usually women are exposed to mobbing, rate of verbal violence is quite high, communication of the employees are prevented in particular, managers exert bullying more, the most effective cause of mobbing is the lack of a safe work environment, and that most of the victimized employees want to quit. It is believed that this study will contribute to the literature by providing a general perspective about the subject.